Student Perceptions of Strengthening and Instilling Character Education Based on the Noble Values of the Indonesian Nation in SB KAMUS Gombok Utara - Maulana, Alam; Rejeki, Sri; Sakban, Sakban; Isnaini, Isnaini (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study investigates the perceptions of SB KAMUS Gombok Utara students regarding the school's efforts to promote character education rooted in the noble values of the Indonesian nation. The effectiveness of character education hinges on students experiencing firsthand the significance of humanism. This research explores how students perceive character education integration with Indonesian national values within their school context. Employing a quantitative approach grounded in descriptive statistics, data was collected through observation, interviews, documentation, and questionnaires. The findings reveal that 62.96% of the 27 participating students felt adequately prepared regarding strengthening character education, while 37.04% were somewhat prepared. Furthermore, 59.26% of the students felt ready regarding the cultivation of character education content based on noble values, while 40.74% were very prepared. Various factors were identified to influence the educational environment, including teacher and parental awareness, consistency in applying noble values, resource limitations, evolving social values, challenges in progress measurement, shifting priorities, and cultural diversity. Despite these challenges, concerted efforts from stakeholders—comprising families, schools, and communities—can surmount obstacles and fortify the youth's development of positive character traits.